Nutrition Optimization through the Application of Fuzzy Logic in Determining the Best Packaged Milk Drinks - Debby Marsela; Briliant Rutmana Siregar; Lintang Putri Salshabila; Mir’atul Azizah; Muhammad Hasan Farid; Sabrina Salsabila; Umratul Umami (Journal of Applied Science, Technology & Humanities | JASTH, 2025)
The application of fuzzy logic in decision making is growing, especially in determining products that meet certain criteria. This study aims to apply the Mamdani fuzzy logic method to recommend the best packaged milk based on protein content and price. Input data in the form of price and protein content are converted into fuzzy sets and processed using MATLAB application. The process of fuzzification, rule determination, inference, and defuzzification produces ideal milk recommendations according to consumer preferences. The results show that products with high protein content and affordable prices have the highest recommendation rate. This method helps consumers in choosing dairy products that suit their nutritional needs and budget.